Towards a vertically separated broadband infrastructure: The potential role of voluntary separation. Issue 2 (June 2020) - Queder, Fabian
Public policymakers face the challenge of maintaining incentives for investments in fiber-to-the-premises (FTTP) infrastructure while simultaneously enabling effective competition. In that regard, the ability of vertically integrated operators to discriminate against downstream rivals is regarded as a major regulatory problem, especially as policing nondiscrimination obligations is notoriously difficult for vertically integrated operators. The European regulatory framework mandates functional separation to eliminate discrimination incentives. However, this measure comes with significant drawbacks and caveats and resembles a strong market and ownership intervention. The present article discusses how voluntary vertical separation can achieve the positive effect of a vertically separated industry structure without the need for strong market interventions. We use a discounted cash flow model to compare the financial attractiveness of wholesale-only and integrated business models for a greenfield FTTP rollout. We further discuss and test how public policymakers could positively affect the profitability of a wholesale-only business model. Based on our findings, we recommend public-policymakers and national regulation authorities to proactively define separation scenarios and respective ex ante regulation reductions precisely, to make adjustments to broadband state aid programs that favor wholesale-only providers, and to critically reflect the hampering effect volume and time discount wholesale tariff structures of incumbents have on the emergence of wholesale-only networks.